Assessing Surgical Task Load and Performance: A Comparison of Simulation and Maritime Operation. (19th February 2020) - Spitzer, Holly V; Hoang, Tuan; Pierce, Eric; Franciose, Reginald J; Pena, Matthew; Shattuck, Nita L; Bass, Cameron R; Blankenship, Jeffrey; Juliano, Michael; Lindemann, Cameron B; Springer, Hayden A; LaPorta, Anthony J
ABSTRACT: Introduction: This study examined the effects of simulated and actual vessel motion at high seas on task load and surgical performance. Methods: This project was performed in phases. Phase I was a feasibility study. Phase II utilized a motion base simulator to replicate vessel motion. Phase III was conducted aboard the U.S. Naval Ship Brunswick. After performing surgical tasks on a surgical simulation mannequin, participants completed the Surgical Task Load Index (TLX) designed to collect workload data. Simulated surgeries were evaluated by subject matter experts. Results: TLX scores were higher in Phase III than Phase II, particularly at higher sea states. Surgical performance was not significantly different between Phase II (84%) and Phase III (89%). Simulated motions were comparable in both phases. Conclusions: Simulated motion was not associated with a significant difference in surgical performance or deck motion, suggesting that this simulator replicates the conditions experienced during surgery at sea on the U.S. Naval Ship Brunswick. However, Surgical TLX scores were dramatically different between the two phases, suggesting increased workload at sea, which may be the result of time at sea, the stress of travel, or other factors. Surgical performance was not affected by sea state in either phase.